PENGGUNAAN COAL FLY ASH (CFA) DAN TANDAN KOSONG KELAPA SAWIT (TKKS) UNTUK PERBAIKAN TANAH ULTISOL DAN SERAPAN LOGAM BERAT - Aryo Candra Nugroho; Amir Hamzah; Hesti Triana Soelistriari (BUANA SAINS, 2020)
Ultisol is the main type of land in Kalimantan, Sumatra, Papua and Sulawesi, with an area of almost 45.8 million ha or 25% of the land area of Indonesia. Ultisol has a relatively high acidity (average pH 4.5), high Al saturation, reaching 60%. The efforts to increase the fertility of ultisol soils such as the addition of organic materials such as Empty Oil Palm Bunches (OPEFB) and CFA (Coal Fly Ash) or Coal Fly Ash (CFA) improve the physical properties of Ultisol soil. Use of CFA that exceeds the limit can cause pollution especially copper (Cu) and lead (Pb). One way to recover soil from heavy metal contaminants with Phytoremediation technology, mustard (Brassica juncea L.) is one of the plants that easily absorb heavy metals so that it can be used as a Phytoremediation agent. The aims of this research to determine the use of CFA and OPEFB to fix up the ultisol soil and heavy metal content absorbed by plants. This study used Completely Randomized Design with 3 replications. The results showed that using of CFA and OPEFB can increase the available P so that it can increase the growth of mustard plants and absorption of heavy metals. By using the dozes of 54.54g CFA and 18.18g OPEFB (C3K1) can increase P- available at 181.67 m kg-1 . The uptake of heavy metals Cu and Pb in mustard plants is very high. The highest uptake in Cu reached 192.03 mg kg-1 , whereas in Pb it was 80 mg kg-1 . This number is still very high, so it is dangerous if consumed.